Chemoprevention and screening in primary sclerosing cholangitis. - Kitiyakara, T; Chapman, R (2008)
Primary sclerosing cholangitis (PSC) is a chronic inflammatory disease that causes fibrosis of the biliary tree. Life expectancy of patients is reduced by liver failure and a high incidence of malignancy. It is closely associated with inflammatory bowel disease, particularly ulcerative colitis, which coexists in approximately three-quarters of northern European patients. Cancers include cholangiocarcinoma, gallbladder cancer, hepatocellular carcinoma, pancreatic cancer and colorectal cancer. Ursodeoxycholic acid appears to reduce the incidence of colorectal neoplasia in patients with PSC, and there is some suggestion that it may also reduce the incidence of cholangiocarcinoma. A chemoprotective benefit of 5-aminosalicylates has not been confirmed in patients with PSC with associated inflammatory bowel disease. There is no accepted screening programme for cholangiocarcinoma, but methods for detecting early disease using biochemical markers, scanning using positron emission tomography or MRI, and endoscopic procedures such as endosonography and endoscopic retrograde cholangiopancreatography are discussed. A combination of techniques is often used in an attempt to diagnose early cholangiocarcinoma. Cholecystectomy should be performed for gallbladder polyps, as many are malignant, and ultrasonography and alpha-fetoprotein testing are suggested for screening for hepatocellular carcinoma. Colorectal carcinoma screening should be performed after the diagnosis of PSC, and surveillance colonoscopy should be performed annually if there is concomitant colitis.